Placental calcifications: a clue for the identification of high-risk fetuses in the low-risk pregnant population?. (18th March 2016) - Mastrolia, Salvatore Andrea; Weintraub, Adi Yehuda; Sciaky-Tamir, Yael; Tirosh, Dan; Loverro, Giuseppe; Hershkovitz, Reli
Abstract: "What does it mean, Doctor?" and "Is it going to affect my baby in some way?". Those are the most typical questions of pregnant women to obstetricians. Answering is sometimes easier but placental calcification is not the case, since placental architecture and disease are two different faces of the same coin and the association between them is not completely clear. Placenta can function properly, even in the presence of architectural alterations, without any fetal consequences. So, remains the question, when does a placental structural anomaly become a sign of increased attention to maternal conditions, fetal development and well-being? The present review will analyze these concepts, with emphasis on placental calcification, its pathogenesis, and the state-of-the-art regarding the influence of this finding on pregnancy outcomes among low-risk pregnant patients.